Diagnosis and Management of Mild Traumatic Brain Injury in Children: A Systematic Review - Lumba-Brown, Angela; Yeates, Keith Owen; Sarmiento, Kelly; Breiding, Matthew J; Haegerich, Tamara M; Gioia, Gerard A; Turner, Michael; Benzel, Edward C; Suskauer, Stacy J; Giza, Christopher C; Joseph, Madeline; Broomand, Catherine; et al. (JAMA pediatrics, 2018)
In recent years, there has been an exponential increase in the research guiding pediatric mild traumatic brain injury (mTBI) clinical management, in large part because of heightened concerns about the consequences of mTBI, also known as concussion, in children. The CDC National Center for Injury Prevention and Control's (NCIPC) Board of Scientific Counselors (BSC), a federal advisory committee, established the Pediatric Mild TBI Guideline workgroup to complete this systematic review summarizing the first 25 years of literature in this field of study. To conduct a systematic review of the pediatric mTBI literature to serve as the foundation for an evidence-based guideline with clinical recommendations associated with the diagnosis and management of pediatric mTBI. Using a modified Delphi process, the authors selected 6 clinical questions on diagnosis, prognosis, and management or treatment of pediatric mTBI. Two consecutive searches were conducted on PubMed, Embase, ERIC, CINAHL, and SportDiscus. The first included the dates January 1, 1990, to November 30, 2012, and an updated search included December 1, 2012, to July 31, 2015. The initial search was completed from December 2012 to January 2013; the updated search, from July 2015 to August 2015. Two authors worked in pairs to abstract study characteristics independently for each article selected for inclusion. A third author adjudicated disagreements. The risk of bias in each study was determined using the American Academy of Neurology Classification of Evidence Scheme. Conclusion statements were developed regarding the evidence within each clinical question, and a level of confidence in the evidence was assigned to each conclusion using a modified GRADE methodology. Data analysis was completed from October 2014 to May 2015 for the initial search and from November 2015 to April 2016 for the updated search. Validated tools are available to assist clinicians in the diagnosis and management of pediatric mTBI. A significant body of research exists to identify features that are associated with more serious TBI-associated intracranial injury, delayed recovery from mTBI, and long-term sequelae. However, high-quality studies of treatments meant to improve mTBI outcomes are currently lacking. This systematic review was used to develop an evidence-based clinical guideline for the diagnosis and management of pediatric mTBI. While an increasing amount of research provides clinically useful information, this systematic review identified key gaps in diagnosis, prognosis, and management.